PENERAPAN METODE TOPSIS DENGAN JARAK EUCLIDEAN TERBOBOT DALAM MENENTUKAN KESESUAIAN PEKERJAAN UNTUK LULUSAN SARJANA - Sayekti, Annisa Nur Afifah Kusuma; Sulaiman, Raden (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
The Open Unemployment Rate (TPT) for Diploma IV, Bachelor’s, Master’s, and Doctoral graduates in Indonesia remains high at 5.52% as of February 2023. This condition highlights the need for solutions to help graduates, particularly computer science bachelor's degree holders, secure suitable jobs. This study aims to provide job references in the technology sector that are in high demand using a Multi-Criteria Decision-Making (MCDM) approach. The method employed is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and its modification, Weighted Euclidean Distance TOPSIS (WED-TOPSIS), to rank jobs based on five criteria: work-life balance, compensation, career opportunities, income, and level of difficulty. Ten technology-related jobs, such as Data Scientist, Machine Learning Engineer, and Software Engineer, were analyzed in this study. WED-TOPSIS was modified by adding weights to the positive and negative ideal solutions to reflect the importance of each criterion. The results indicate that WED-TOPSIS outperforms standard TOPSIS by providing rankings more aligned with the selected criteria priorities. This research is expected to serve as a guide for graduates in choosing appropriate jobs and help reduce unemployment among bachelor’s degree holders.